Students’ Perspective on the Role of Digital Flashcards in Building Vocabulary Skills - Maulani, Farah Nabilah Febry; Muhtarom; Latiefah, Junaenik (ICONELT, 2024)
Vocabulary is an important component that must be mastered to support English language skills such as reading, speaking, listening, and writing. Vocabulary mastery is knowledge that involves meaning therefore it is a key to success in understanding a meaning. This study asks the research question: what are students’ attitudes towards using digital flashcard in vocabulary learning? The purpose of this study is to investigate the perspective of secondary students about the developing vocabulary skills using digital flashcards. Than the principle of flashcards in language learning is well known, digital flashcard applications has gained popularity recently. This research use qualitative study aims to explore how attitudes of students online vocabulary learning digital flashcards. The result of this study will contribute to the understanding of the pros, cons, and overall learner experience of students at the full stack coarse from vocabulary flashcard on their device.